The tax treatment of homeowners and landlords and the progressivity of income taxation - Matthew Chambers; Carlos Garriga; Don Schlagenhauf (Federal Reserve Bank of Atlanta, 2008)
This paper analyzes the connection between the asymmetric tax treatment of homeowners and landlords and the progressivity of income taxation using a quantitative overlapping generations general equilibrium model with housing and rental markets. Our model emphasizes the determinants of tenure choice (owning versus renting) and the household decision to supply housing services to the rental market. This formulation breaks the link between the rental price and the equilibrium interest rate. Hence, the aggregate supply of rental property responds differently to the direction of rental price changes, marginal tax rate changes, and maintenance cost changes. We show that the model replicates the key factors and the distributional patterns of ownership, house size, and landlords. The degree of progressivity in the income tax code has important implications for housing tenure and housing consumption. We find that a movement toward a less progressive income tax code can generate sizable increases in homeownership and welfare that result from the equilibrium effects and a portfolio reallocation mechanism absent in economies with single assets (e.g., Conesa and Krueger 2006). We find that the removal of existing asymmetries in the tax code has effects on housing that differ from those reported in the literature. We show that housing policy can increase the ownership rate of a particular segment of the population but generate nontrivial distributional costs. The welfare increases are no larger than those found when the progressivity of the tax code is reduced.
Keywords: E2; E6; R2; 330; homeownership; rental markets; housing policy; tax policy